Pentingnya Pemanfaatan Teknologi Informasi Oleh Guru Bimbingan dan Konseling - Triyono Triyono; Rahmi Dwi Febriani (Jurnal Wahana Konseling, 2018)
ABSTRAK Teknologi informasi merupakan faktor penting dalam proses pelayanan BK. Adanya pemanfaatan teknologi informasi diharapkan dapat mendorong guru BK/konselor untuk lebih kreatif, inovatif, variatif dalam mencari informasi terbaru dalam proses pelayanan. Oleh sebab itu, teknologi hasus dimanfaatkan dengan sebaik dan seoptimal mungkin oleh guru BK/konselor agar pelayanan yang diberikan bisa memberikan hasil yang optimal. Agar teknologi bisa dimanfaatkan secara optimal maka tidak akan terlepas dari kemauan, pengetahuan, dan keterampilan guru BK/konselor dalam memanfatkannya untuk proses pelayanan. Guru BK/konselor yang memiliki pengetahuan dan keterampilan maka akan cenderung memanfatkan teknologi informasi dalam pelayanan bimbingan dan konseling.Kata Kunci: Teknologi informasi, guru, bimbingan dan konseling.  THE IMPORTANCE OF UTILIZING INFORMATION TECHNOLOGY BY TEACHER AND CONSELING TEACHERS ABSTRACT Technology information is an important factor in the process of guidance and counselling services. The existence of the utilization of technology information is expected to encourage teachers of guidance and counseling for a more creative, innovative, and varied in finding and providing the latest information in the process of counselling. Therefore, technology should be put to my best optimal and perhaps by the teacher guidance and counseling so that the given service can give you optimal results. However, the situation there is still the fact teacher guidance and counselling have yet to utilize technology information optimally. While technology information is one of the factors supporting the ministry of guidance and counseling. So the technology can be utilized optimally then there will be regardless of the will, knowledge, and skills of the teacher guidance and counseling in the figure for service of process. Teacher guidance and counselling have the willingness, knowledge, and skills it will tend to also take advantage of technology information in the service of guidance and counseling. Keyword: Technology information, teacher, guidance and counseling.